The Leadership Model of Reje in Preserving The Customs and Cultural Identity of The Gayo Ethnic - Syahputra, Muhammad Rizki; Rifa'i, Muhammad; Chaniago, Nasrul Syakur; Zendah, Ali Abedlqader Ali (Institut Agama Islam Negeri Lhokseumawe, 2025)
This study investigates the role of Reje leadership in preserving the customs and cultural identity of the Gayo community in Kampung Keramat Mupakat. Utilizing a descriptive-analytical qualitative approach, the research examines the meanings, values, and practices of Reje leadership across four dimensions: religious, justice, cultural, and participatory. Data were collected through in-depth interviews, participatory observations, and the review of customary documents, and analyzed using the Miles, Huberman, and Saldaña model. The findings reveal that Reje leadership is grounded in the principle of (